Common sources of radiations in a medical environment - Sharma, Harshvardhan; Gaur, Pradeep; Gupta, Devesh; Rajpurohit, Vikas (International Journal of Research in Medical Sciences, 2021)
Use of radiation is now a days so common in most of the tertiary care hospitals for diagnostic and therapeutic purpose. The ionizing radiation provides many benefits in both diagnostic as well as therapeutic interventions, but they are also potential harmful. Radiation risks, exposure and mitigation strategies should always be in mind while using to an individual (public, radiation worker, and patient) and the environment should not exceed the prescribed safe limits. Regular monitoring of hospital area and radiation workers is mandatory to assess the quality of radiation safety. This review article emphasis on radiation risks, exposure and prevention and treatment strategies.